c-MAF, a Swiss Army Knife for Tolerance in Lymphocytes - Imbratta, Claire; Hussein, Hind; Andris, Fabienne; Verdeil, Grégory (Frontiers in Immunology, 2020)
Beyond its well-admitted role in development and organogenesis, it is now clear that the transcription factor c-Maf has owned its place in the realm of immune-related transcription factors. Formerly introduced solely as a Th2 transcription factor, the role attributed to c-Maf has gradually broadened over the years and has extended to most, if not all, known immune cell types. The influence of c-Maf is particularly prominent among T cell subsets, where c-Maf regulates the differentiation as well as the function of multiple subsets of CD8 and CD4 T cells, lending it a crucial position in adaptive immunity and anti-tumoral responsiveness. Recent research has also revealed the role of c-Maf in controlling Th17 responses in the intestine, positioning it as an essential factor in intestinal homeostasis. This review aims to present and discuss the recent advances highlighting the particular role played by c-Maf in T lymphocyte differentiation, function and homeostasis.